Online Fees Clearance System For Uganda Martyrs University Kabale-Campus. - Niwabiine, Doreen (Kabale University, 2024)
The system is aimed at alleviating the various problems and stress involved in the manual method of fee clearance. Moreover, the issue of delayed service as a result of the inability to complete the tedious manual process of clearance would be curtailed. The online fee clearance system is designed to help a student pay all their dues and obtain a clearance certificate. Hence it became imperative for an online fee clearance system to eliminate the shortcomings of the manual system in place. The main objective of the project is to develop a user-friendly online fee clearance system for Uganda Martyrs University Kabale campus